2019
DOI: 10.1101/668665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The identification of mecciRNAs and their roles in mitochondrial entry of proteins

Abstract: Mammalian mitochondria have small genomes encoding very limited numbers of proteins. Over one thousand proteins and noncoding RNAs encoded by nuclear genome have to be imported from the cytosol into the mitochondria. Here we report the identification of hundreds of circular RNAs (mecciRNAs) encoded by mitochondrial genome. We provide both in vitro and in vivo evidence to show that mecciRNAs facilitate mitochondrial entry of nuclear-encoded proteins by serving as molecular chaperones in the folding of imported … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…However, some studies have also shown that EIciRNAs and ciRNAs can enhance the transcription and splicing of their parental genes by interacting with RNA polymerase II (pol II) or the essential splicing factor U1 small nuclear ribonucleoprotein (snRNP) [61,62]. Hundreds of circRNAs, encoded by the mitochondrial genome (mecciRNA) in both human and mouse cells, were recently identified [63]. The study found that some mec-ciRNAs can act as molecular chaperones to facilitate mitochondrial transport of proteins encoded by nuclear genes, which is essential for mitochondrial adaptation to physiological conditions.…”
Section: Overview Of Circrnasmentioning
confidence: 99%
“…However, some studies have also shown that EIciRNAs and ciRNAs can enhance the transcription and splicing of their parental genes by interacting with RNA polymerase II (pol II) or the essential splicing factor U1 small nuclear ribonucleoprotein (snRNP) [61,62]. Hundreds of circRNAs, encoded by the mitochondrial genome (mecciRNA) in both human and mouse cells, were recently identified [63]. The study found that some mec-ciRNAs can act as molecular chaperones to facilitate mitochondrial transport of proteins encoded by nuclear genes, which is essential for mitochondrial adaptation to physiological conditions.…”
Section: Overview Of Circrnasmentioning
confidence: 99%
“…F-circrna is synthesized from the transcribed exons of several nuclear genes as a result of chromosomal translocation (36). lastly, meccirna is produced from mitochondrial genes (37). ecircrnas are the most common type of circrna.…”
Section: Classificationsmentioning
confidence: 99%
“…So circRNAs are mainly classified in exonic circular RNA (eciRNA), intronic circular RNA (ciRNA), and exon-intron circular RNA (EIciRNA). But recently, circRNAs from mitochondria DNA were newly investigated, this kind of circRNA was called mecciRNAs [ 26 ]. Because circRNAs have no free 5′cap and 3′ poly A tail, it makes them not easily degraded by RNase.…”
Section: The Specific Roles Of Lncrna Circular Rna and Mirnamentioning
confidence: 99%